Autoeficácia, números de pontos de dor, incapacidade e intensidade relacionada a dor em pessoas idosas com dor lombar crônica inespecífica: análise secundária do ensaio clínico randomizado aleatorizado - Neves dos Santos, Elen Juliana (Universidade Federal de São Carlos, 2024)
Chronic low back pain (CLBP) is the most prevalent, affecting 40% of the Brazilian population, and 20 to 25% of the population over 60 years of age, being one of the main causes of leaves of absence, disability retirement, low productivity and absenteeism at work. , generating a great demand for the healthcare system, making it a public health problem. Biopsychosocial in nature, it often requires a multidisciplinary approach, and psychological factors have been significant in the complaints of patients with CLBP. Considering that pain is influenced by physical, psychological and social factors, treatment should not be restricted only to the biomedical model and pain relief, but should emphasize elements that are obstacles to recovery and return to daily life and social activities. We must highlight the importance of an assessment that addresses psychological aspects, therefore, we cannot fail to include the assessment of self-efficacy, considered as a protective factor, self-efficacy can become a powerful mediator between musculoskeletal pain and its established disabilities. Objective: To analyze whether there is a correlation between self-efficacy and the number of pain points in elderly people with CLBP. Methodology: Cross-sectional study, secondary analysis of the controlled and randomized clinical trial, which compared Functional Cognitive Therapy (CBT) with the Solo Pilates Method (MPS). Results: the sample was mostly female, with an average age of 70 years. Regarding self-efficacy, participants presented high self-efficacy (average of 38 points) and a low number of pain points (average of 6 points). In the Pearson correlation test, there was no correlation between self-efficacy and number of pain points (p=0.414). Conclusion: We can conclude that there was no correlation between the variables self-efficacy and number of pain points. The older people who participated in this study showed high self-efficacy.
Self-efficacy, number of pain points, disability and pain-related intensity in older people with chronic non-specific low back pain: secondary analysis of the randomized controlled trial
Keywords: Dor crônica; Dor lombar; Autoeficácia; Idoso; Chronic pain; Low back pain; Self-efficacy; Older people; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE